2014
DOI: 10.3892/ol.2014.1851
|View full text |Cite
|
Sign up to set email alerts
|

Abundant expression of HMGB1 in human T-cell lymphotropic virus type I-infected T-cell lines and high plasma levels of HMGB1 in patients with adult T-cell leukemia

Abstract: High mobility group box 1 (HMGB1) functions as a chromatin-associated nuclear protein and an extracellular signaling molecule. The concentration of HMGB1 protein and the expression of HMGB1 mRNA were analyzed by ELISA and polymerase chain reaction (PCR), respectively. The present study reports high plasma HMGB1 levels in patients with adult T-cell leukemia [ATL; which is caused by infection with human T-cell lymphotropic virus type I (HTLV-I)] compared with normal controls. In addition, HMGB1 was highly expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our data showed that HMGB1 and HMGB2 were more abundant in samples from HTLV-1-infected individuals, markedly in HAM/TSP patients (Supplemental Table 1 ). According to literature, HMGB1 levels are also increased in ATLL patients and HTLV-1-infected cell lines 33 , which corroborates our findings.…”
Section: Resultssupporting
confidence: 93%
“…Our data showed that HMGB1 and HMGB2 were more abundant in samples from HTLV-1-infected individuals, markedly in HAM/TSP patients (Supplemental Table 1 ). According to literature, HMGB1 levels are also increased in ATLL patients and HTLV-1-infected cell lines 33 , which corroborates our findings.…”
Section: Resultssupporting
confidence: 93%
“…After treatment with the HMGB1 inhibitor glycyrrhiza, the invasion and metastatic abilities of lymphoma cells were significantly decreased [139]. Adult T cell leukemia (ATL) patients have high plasma HMGB1 levels compared with normal controls [140]. It has been reported that high plasma HMGB1 levels in patients with ATL are caused by infection with human T cell lymphotropic virus type I (HTLV-I) [141].…”
Section: Lymphomamentioning
confidence: 99%
“…Malignancies of B-cell origin were the most commonly studied, including non-Hodgkin’s lymphoma (NHL) [ 19 21 ] and lymphocytic leukaemias [ 22 24 ]. A minority of studies investigated HMGB1 and RAGE in T-cell malignancies [ 25 , 26 ] and acute myeloid leukaemia (AML) [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two included studies investigated the clinical value of HMGB1 in T-cell-derived haematological malignancies [ 25 , 26 ]. Plasma HMGB1 levels collected upon admission from patients diagnosed with adult T-cell leukaemia tended to be higher than those of healthy donors ( p = 0.051) [ 25 ]. While this study was affected by a small sample size (total, n = 13), the mean level of HMGB1 in patients with T-cell leukaemias was over ten-fold higher than that of healthy donors.…”
Section: Resultsmentioning
confidence: 99%